Unreliable witness: the flaneur as artist and spectator of art in 19th-century Paris - Wrigley, Richard (Oxford University Press, 2016)
The article shows that the well-established association of the flaneur with art, artists is mistaken by reviewing the major primary source texts. It offers an alternative reading of the invention of the flaneur, arguing that it is rooted in early 19th-century journaliastic practices, designed to deal with censorship, and to express political opposition through urban observation.